ANALISIS PENGARUH MOTIVASI DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR PADA MATA KULIAH PERAWATAN WAJAH DAN TEKNOLOGI MAHASISWA KONSENTRASI TATA RIAS JURUSAN PENDIDIKAN KESEJAHTERAAN KELUARGA FT UNM - Wildan Auliah Moh. Natsir; Hamidah Suryani; Syamsidah (UNM Journal of Technology and Vocational, 2022)
The aims of the study are to discover (1) the description of the learning outcomes of Facial Care and Technology Course with a concentration in cosmetology, (2) the description of learning motivation on learning outcomes in Facial Care and Technology Course, (3) the description of learning facilities in Facial Care and Technology Course, (4) the influence of students’ learning motivation on learning outcomes in Facial Care and Technology Course, (5) the influence of learning facilities on learning outcomes in Facial Care and Technology Courses, and (6) the extent of the influence of motivation and learning facilities on learning outcomes in Facial Care and Technology Course in the PKK Department of FT UNM. The type of this study is a quantitative correlational research and the sampling technique used is purposive sampling technique, so the sample of the study is 15 people. Data collection techniques employed questionnaires and documentation. Data analysis of the study employed descriptive analysis, classical assumption test, and hypothesis testing. The results of the study reveal that (1) the learning outcomes of Facial Care and Technology Course is in very high category, (2) the students’ motivation in Facial Care and Technology Course is in high category, (3) the learning facilities in Facial Care and Technology Course are in high category, (4) the learning motivation has a significant influence on learning outcomes in Facial Care and Technology Course, (5) the learning facilities have a significant influence on learning outcomes in Facial Care and Technology Course, and (6) the motivation and learning facilities collectively have a significant influence on learning outcomes in Facial Care and Technology Course in the PKK Department of FT UNM.